Efficacy of music therapy for depressive symptoms in college students: a meta-analysis and systematic review - Lin, Yanru; Li, Qianlong (Frontiers in Psychology, 2025)
IntroductionIn China, Depression is a significant mental health issue among college students, with a 28.4% prevalence rate. This meta-analysis systematically synthesizes empirical data to evaluate the therapeutic efficacy of music therapy in mitigating depressive symptoms within collegiate populations.MethodsTwo authors searched seven international and Chinese databases from inception to February 5, 2025, for randomized controlled trials (RCTs) on music therapy for college students with depressive symptoms. Statistical synthesis was performed with RevMan 5.3 software, using random-effects models to calculate standardized mean differences (SMDs) with 95% confidence intervals.ResultsSixteen RCTs involving 938 participants were included. Pooled estimates showed significant reductions in depressive symptoms as measured by SDS (SMD = −1.19, 95% CI: −1.56 to −0.82; p < 0.001), SCL-90 depression subscale (SMD = −1.29, 95% CI: −1.96 to −0.62; p = 0.002), and BDI (SMD = −1.98, 95% CI: −3.59 to −0.38; p = 0.015). High heterogeneity (I2 = 76–89%) was found, but the results remained robust even after undergoing sensitivity analyses.ConclusionMusic therapy is an effective adjunctive intervention for managing depressive symptoms in college students. However, due to significant heterogeneity, future research needs standardized treatment frameworks. Multi-center RCTs with blinded assessment and longitudinal designs should be prioritized to clarify dose-response relationships and neurophysiological mechanisms, facilitating the integration of music therapy into evidence-based mental health strategies for this population.